Pelatihan Penggunaan Software Mendeley Pada Mahasiswi Program Studi Matematika Universitas Annuqayah dalam Menyusun Karya Ilmiah - Sarifah, Luluk; Khotijah, Siti; Purnama, Prasanti Mia (Universitas Islam Madura, 2025)
Mendeley is a software that can be used to simplify writing citations and creating bibliographies automatically. The purpose of this community service activity is to improve the insight, writing skills and quality of students' scientific work. This community service consists of three stages, namely preparation, implementation and evaluation, where the implementation stage is divided into 2 sessions, namely the material delivery session through the lecture method, then the training/practice and mentoring session. The results of the activity indicate an increase in students' understanding and skills in using Mendeley. Prior to the training, approximately 90% of the Mathematics students who attended the training did not know or understand how to enter references and citations using mendeley, as most were still using manual methods. However, after attending the training and going through the evaluation phase, 100% of participants were able to successfully implement the material independently